Fine structural changes of Rohu {Labeo rohita) sperm after dilution with cryoprotectants - Gopalakrishnan, A; Ponniah, A G; Lal, Kuldeep K (Indian Journal of Fisheries, 2011)
Spermatozoa of rohu (Laheo rohita) were diluted in two cryodiluents and finestructural changes were investigated. Damages were observed in head, mid-pieceand tail of about 51% spermatozoa immediately after dilution in one of thecryodiluents. After 10 minutes of equilibration period, the frequency of damagedsperms increased to 85%. The other diluent did not exhibit significant structuralchanges unlike the former one and nearly 60% sperms remained visibly intact evenafter 10 minutes of equilibration time. The present investigation points out (1)diluents inhibiting sperm motility alone need not always be ideal for a species and(2) usefulness of ultrastructural images offish sperms in determining the fertilizingability of milt and in preliminary screening and selection of cryodiluents for deepfreezingprogrammes.